2021
DOI: 10.52910/ajhs.12
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice Regarding Menstruation among the Visually Challenged Female Students of Westen Nepal

Abstract: Background: Menstruation is part of the female reproductive cycle starts when girls become sexually mature at the time of puberty.. A visually challenged female faces daily extra challenges for bearing their everyday skills including menstruation hygiene management. Hygienic practices during menstruation are very important as poor menstruation affects the health by increasing vulnerability to infections This study aims to assess the knowledge and practices regarding menstruation among the visually challenged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…There was no significant association between the level of knowledge related to menstrual hygiene in age, education, family type, occupation of the father, family income, age at first menstruation, pre-existing knowledge and source of information (p> 0.05). This study supports the finding of the present study [10] . There was no significant association between the pre-test level of knowledge and demographic variables such as age in years, age of menarche, educational status of the student, educational status of the parents, occupation of parents, type of family, family monthly income, religion, any prior information regarding menstruation except educational status of the student.…”
Section: Resultssupporting
confidence: 94%
“…There was no significant association between the level of knowledge related to menstrual hygiene in age, education, family type, occupation of the father, family income, age at first menstruation, pre-existing knowledge and source of information (p> 0.05). This study supports the finding of the present study [10] . There was no significant association between the pre-test level of knowledge and demographic variables such as age in years, age of menarche, educational status of the student, educational status of the parents, occupation of parents, type of family, family monthly income, religion, any prior information regarding menstruation except educational status of the student.…”
Section: Resultssupporting
confidence: 94%
“…However, research has shown that teachers lack training and con dence in providing information and a positive environment for students to understand the menstrual cycle beyond a purely biological perspective [11]. In cases where teachers are enthusiastic about assisting students, schoolgirls may always prefer their mothers to be their primary source of information about menstrual hygiene management practices [12], perhaps due to the lack of trust in the school system to assist them without a cause for stigma.…”
Section: Introductionmentioning
confidence: 99%